PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN KEKERASAN SEKSUAL: Indonesia - Mohamad Faisal Aulia; Siah Khosyiah (Universitas Islam Negeri Raden Fatah Palembang, 2021)
The purpose of this study was to find out the legal form of protection for child victims of sexual violence in the South Central Timor district of NTT. This research is a normative research using the method of statutory approach. The location of this research is in the Social Service of South Central Timor Regency. data collection techniques using library research and interviews. The results of the research in this discussion have been explained in Law No. 35 of 2014 concerning amendments to Law No. 23 of 2002 concerning Child Protection in Article 59A regarding medical, psychosocial, social, and judicial assistance. Article 67B concerning guidance, assistance, and social recovery of mental and physical health and Article 69A concerning education, social rehabilitation, psychosocial assistance, and assisting the judicial process.As for Law no. 31 of 2014 concerning Amendments to Law No. 13 of 2006 concerning Protection of Witnesses and Victims Article 5 concerning the rights of witnesses and victims, Article 6 concerning medical assistance, and psychosocial and psychological rehabilitation, and Article 10 concerning witnesses and/or victims cannot be prosecuted legally. Then Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Legal protection for child victims of sexual violence provided by the Social Service is a form of assistance that begins when the child becomes a victim and the victim can return to the community. Sexual violence receives free assistance from the social service and social rehabilitation center for children who need special protection (BRSAMPK). include; medical, psychological, social and judicial. Keywords: Sexual Violence, Special Protection For Children